INTRODUCTION - Mohd Azlan, Jayasilan; Arianti, Atong; Abang Arabi, Abang Aimran; Indraneil, Das (UNIMAS Publisher, Sarawak Forestry Corporation and Natural History Publications (Borneo) Sdn. Bhd., 2025)
Niah National Park, situated approximately 16 km inland from Sarawak’s north coast and around 85 km south of Miri city in the Miri Division, is celebrated for its extensive limestone caves, rich biodiversity and prehistoric archaeological sites. The National Park protects over 31 km2 with mount Subis being the highest peak in this area (394 m above sea level). Acknowledged as one of Malaysia’s most important archaeological and natural sites, Niah was inscribed as a UNESCO World Heritage Site at the 46th World Heritage Committee Meeting held in Delhi, India, in 2024. This designation recognizes the Park’s outstanding universal value, highlighting the longest-known record of human interaction with tropical rainforests, dating back more than 50,000 years to the Mid-Holocene period. The Niah Caves Complex preserves archaeological evidence that provides a unique insight into cultural traditions of ancient populations spanning from the Pleistocene to the Mid-Holocene, showcasing early human settlement and land use in Southeast Asia. With this designation, Sarawak now stands out as the only state in Malaysia with two UNESCO.